Genome Sequencing of Ralstonia solanacearum CQPS-1, a Phylotype I Strain Collected from a Highland Area with Continuous Cropping of Tobacco - Liu, Ying; Tang, Yuanman; Qin, Xiyun; Yang, Liang; Jiang, Gaofei; Li, Shili; Ding, Wei (Frontiers in Microbiology, 2017)
Ralstonia solanacearum, an agent of bacterial wilt, is a highly variable species with a broad host range and wide geographic distribution. As a species complex, it has extensive genetic diversity and its living environment is polymorphic like the lowland and the highland area, so more genomes are needed for studying population evolution and environment adaptation. In this paper, we reported the genome sequencing of R. solanacearum strain CQPS-1 isolated from wilted tobacco in Pengshui, Chongqing, China, a highland area with severely acidified soil and continuous cropping of tobacco more than 20 years. The comparative genomic analysis among different R. solanacearum strains was also performed. The completed genome size of CQPS-1 was 5.89 Mb and contained the chromosome (3.83 Mb) and the megaplasmid (2.06 Mb). A total of 5229 coding sequences were predicted (the chromosome and megaplasmid encoded 3573 and 1656 genes, respectively). A comparative analysis with 8 strains from four phylotypes showed that there was some variation among the species, e.g., a large set of specific genes in CQPS-1. Type III secretion system gene cluster (hrp gene cluster) was conserved in CQPS-1 compared with the reference strain GMI1000. In addition, most genes coding core type III effectors were also conserved with GMI1000, but significant gene variation was found in the gene ripAA: the identity compared with strain GMI1000 was 75% and the hrpII box promoter in the upstream had significantly mutated. This study provided a potential resource for further understanding of the relationship between variation of pathogenicity factors and adaptation to the host environment.